2008
DOI: 10.1157/13120394
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of allergic rhinitis and atopic dermatitis in children

Abstract: Allergic disorders are the chronic diseases of greatest pediatric morbidity, affecting over 25 % of the pediatric population. Indeed, this situation has been referred to as an "allergic epidemic". In comparison with asthma, atopic dermatitis and allergic rhinitis have been less extensively investigated, although this does not mean that they should be regarded as minor disorders but rather as alterations that affect the quality of life of the patients and their families, which generate considerable direct and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 121 publications
1
19
1
2
Order By: Relevance
“…The rate of autoimmune and hypersensitivity diseases in human beings is on the order of 3–20% of the adult population, respectively (Cooper and Stroehla, 2003; Torres-Borrego et al, 2008), and this implies that, at least in modern society, a loss of immune regulation is common. With respect to autoimmunity mediated by the adaptive immune system, there are at least three mechanisms that moderate self-reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of autoimmune and hypersensitivity diseases in human beings is on the order of 3–20% of the adult population, respectively (Cooper and Stroehla, 2003; Torres-Borrego et al, 2008), and this implies that, at least in modern society, a loss of immune regulation is common. With respect to autoimmunity mediated by the adaptive immune system, there are at least three mechanisms that moderate self-reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…This variation cannot be explained solely with genetic factors. Genetic and geographical factors and interaction between changes in life and nutrition styles are also influential [19,21,22,23]. It has also been reported that this variation does not occur at the same rate when the allergic diseases are evaluated separately.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of these diseases has considerably increased worldwide in recent years, especially in some regions of Latin America [3-5]. The causes of this increase are not fully understood, some hypotheses are related to changes in lifestyle and environmental and domestic factors [6,7] that interact with the immune system in early stages of life [8]. …”
Section: Introductionmentioning
confidence: 99%